Health Survey in Suphan Buri Province 2007 - Yaemla-or, Sineenat; Songkroh, Mullika (Journal of Health Science of Thailand, 2018)
The purposes of this survey research were to study health status of the population in Suphan Buri in a situation analysis, as such, evaluation of health promotion programs become possible. Data collected by interviewing 1,200 study samples in 15-59 year age group selected by multi-stage random sampling with unequal probability (probability proportional to size) including 60 clusters. Descriptive statistics were used for data analysis. The health survey identified high risks of the 15-59 year age group relative to older age groups, in terms of obesity, being physically inactive, limited to less than 3 days a week or no exercise at all. As a result, 67.3 percent of the physically inactive were classified as limited or no exercise. Repeatedly, 40.7 percent of the male subjects were regular smokers and 12.8 percent regular drinker. Such indulgence was reported in only 1.5 percent of the female subjects. Screening for hypertension might relatively yield the best coverage as 67.2 percent of the subjects received the service while 43.4 and 21.7 percent had such services for diabetic mellitus and serum cholesterol. Among the female, 55.5 percent had experiences on self examination of breast cancer, 29.0 percent were examined by health workers and 70 percent had undergone screening for cervical cancer. High level of stress was reported in 2 percent of the samples. In addition, 98.8 percent of them were eligible to the UC benefit and satisfied with services of health centers than those of designated hospitals. Change of health behaviors focusing on nutrition and exercise should become crucial part of the strategic plan on health promotion in Suphan Buri. Youths should be considered the target as well as a mechanism in promotion campaigns. On the other hand, males roles on community health promotion should also be strengthened.